Nano-composite ceramic coating liquid and preparation method thereof

By using nano -composite ceramic coating, it contains nano -grade powder such as alumina and silicate, forming ceramic coating, which solves that the existing coating is difficult to have high insulation resistance coefficients, good adhesion, corrosion resistance, heat resistance, heat resistance Performance issues realize environmental friendly high -performance ceramic coatings.

CN119331439APending Publication Date: 2025-01-21HANGZHOU KEDE MAGNETOELECTRIC CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411409517.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

It is difficult for the semi-inorganic ceramic coating on the surface of existing steel strips to have high insulation resistance, good adhesion, corrosion resistance, heat resistance and environmental friendliness at the same time.

Method used

Using nano -composite ceramic solution, contains nano -grade powder such as alumina, silicate, stable oxide oxide, silicon oxide, and high -expanded glass powder. coating.

Benefits of technology

The ceramic coating achieves high adhesion, heat resistance, corrosion resistance and high insulation resistance coefficient on the soft magnetic alloy strip, while avoiding the use of heavy metal elements and being environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure BDA0005077607900000061
    Figure BDA0005077607900000061
Patent Text Reader

Abstract

The invention relates to the technical field of metal surface treatment, in particular to nano-composite ceramic coating liquid and a preparation method thereof. According to the nano-composite ceramic coating liquid, high-expansion glass powder is matched with zirconium oxide stabilized by silicon oxide and yttrium oxide, so that the expansion coefficient of filler of a prepared ceramic coating layer is in gradient change under the action of thermal shock, the internal stress of the ceramic coating layer is reduced, and the ceramic coating layer and a magnetically soft alloy base material have relatively good synchronism; the adhesion performance of the ceramic coating is further improved; furthermore, a coupling agent containing hydroxyl and / or amino is adopted in the nano-composite ceramic coating liquid, so that the stability and uniformity of the ceramic coating are improved, and an adhesion promoter promotes the dispersion performance of each component of the nano-composite ceramic coating liquid; the prepared ceramic coating is thin and environment-friendly, and has the advantages of high surface insulation resistance coefficient, high adhesiveness, good corrosion resistance, good hardness and good high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of metal surface treatment, and in particular to a nano-composite ceramic coating solution and a preparation method thereof. Background Art

[0002] Soft magnetic alloy strip is one of the important functional metal materials, including industrial pure iron, electrical steel, Permalloy and Fe-Co alloy strip, etc. Most of these alloy strips are used to prepare stator and rotor laminations (iron core) of motors. The strip surface needs to have an insulating layer to increase the insulation performance between the iron core layers, so as to improve the insulation resistivity between the iron cores and reduce the eddy current loss generated when the iron core is working. At the same time, the coating needs to meet good adhesion, punching and shearing processability and temperature resistance to ensure the long-term operation stability and service life of high-speed motors.

[0003] At present, the coating process of cold-rolled oriented and non-oriented electrical steel is very mature. Organic coatings, inorganic coatings, and semi-inorganic coatings suitable for various environments have been industrialized. After the organic coating is formed, the strip has good punching and shearing properties, but the surface insulation resistance coefficient is not high, the hardness is low, the wear resistance and heat resistance are poor, and it is not environmentally friendly. After the inorganic coating is formed, it has good heat resistance, but the machinability and adhesion are poor, and the surface insulation resistance coefficient is low. After the semi-inorganic coating is formed, its comprehensive performance is good. It is the main type of coating used by non-oriented electrical steel manufacturers at home and abroad, including Wuhan Iron and Steel's T4 coating (surface insulation resistance coefficient> 1000Ω·mm 2 / piece), Anshan Iron and Steel's TM4 coating, Baosteel's A, H, K coatings, and Taigang's TC and TE series coatings. For TC coating, its surface insulation resistance coefficient is relatively low (> 100Ω·mm 2 / piece), L, L2, L3 coatings of Nippon Steel in Japan, and TW1 coatings of Novolipetsk in Russia. Most of these semi-organic coating products contain chromium coatings. Hexavalent chromium compounds can cause great pollution to the environment and are highly toxic and carcinogenic. Nippon Steel's L, L2, and L3 coatings all contain dichromate, and their corresponding surface insulation resistance coefficients are 700-5000Ω·mm 2 / piece, 150-430Ω·mm 2 / piece, 4000-9000Ω·mm 2 / piece, the difference is quite large.

[0004] Permalloy and Fe-Co alloy have high magnetic permeability and high saturation magnetic induction intensity respectively. Most of the finished products are used in small transformers, pulse transformers, relays, mutual inductors, magnetic amplifiers, electromagnetic clutches, choke cores and magnetic shielding in weak or medium magnetic fields. However, the surface of the soft magnetic alloy strips sold domestically and abroad has not been insulated, which makes the eddy current loss problem of Permalloy and Fe-Co soft magnetic alloy stator and rotor cores more prominent in AC frequency conversion environment. The traditional process for producing Permalloy and Fe-Co soft magnetic alloy stator and rotor laminated cores is: Soft magnetic alloy strip → wire cutting / laser cutting / stamping single piece → cleaning → heat treatment → glue spraying and lamination → machining → lamination iron core finished product. The traditional lamination production process has the following problems: (1) The consistency of the glue layer thickness is unstable and the glue spraying efficiency is low, and the insulation resistance coefficient between sheets varies greatly.

[0005] (2) The acetal drying glue used is an organic polymer, which has poor temperature resistance, resulting in the laminated iron core being unable to be directly heat treated.

[0006] (3) The glue layer overflowing from the outside of the finished product is difficult to grind during the processing, and the processing will also cause a large degree of performance degradation of the laminated iron core.

[0007] (4) The uneven contour of the inner side of the laminated core makes it difficult to remove the overflowed glue layer.

[0008] (5) Due to the unevenness of the glue spraying, interlayer cracking occurs in the laminated core after curing, resulting in a decrease in the qualified rate.

[0009] At present, the insulation resistance coefficient of the semi-inorganic ceramic coating on the surface of electrical steel strip is not high, and the differences are large, and it contains a lot of heavy metal chromium. There is no insulating ceramic coating on the surface of Permalloy and Fe-Co alloy strips. It is necessary to develop a coating liquid that can be used for different types of soft magnetic alloy strips. The coating liquid does not contain heavy metal elements. At the same time, the ceramic coating has a high surface insulation resistance coefficient, adhesion, corrosion resistance and heat resistance. Summary of the invention

[0010] In order to solve the problem that the existing semi-inorganic ceramic coating on the surface of steel strip is difficult to have high surface insulation resistance, adhesion performance, corrosion resistance, heat resistance and environmental friendliness at the same time, the present invention provides a nano-composite ceramic coating and a preparation method thereof.

[0011] In a first aspect, the present application provides a nanocomposite ceramic coating liquid: A nano-composite ceramic coating liquid, which comprises, by weight percentage of the coating, a base liquid, 0.1-5% of a dispersant, 2-15% of a coupling agent, 0.1-1% of an adhesion promoter, 0.2-12% of an emulsifier, 0.1-1.0% of a mildew preventer, 3-20% of a filler and the remainder of a solvent; The base liquid, in terms of percentage by weight of the coating, comprises 3-15% alumina, 3-25% silicate and 20-35% solvent; The filler, in terms of percentage by weight of the coating, comprises 2-20% of a nano-scale yttria-stabilized zirconium oxide and silicon oxide mixed powder and 1-5% of a high expansion glass powder; The adhesion promoter is cage-shaped polysilsesquioxane; the coupling agent is at least one of hydroxyl-terminated polydimethylsiloxane and aminopolydimethylsiloxane.

[0012] Preferably, the particle size of the yttria-stabilized zirconia, silicon oxide, high expansion glass powder, aluminum oxide, and silicate is 20-100 nm.

[0013] By adopting the above technical scheme, the nanocomposite ceramic coating liquid is roller coated or sprayed on the surface of the soft magnetic alloy substrate, and then heated to form a film and heat treated to form a ceramic coating; silicate makes the ceramic coating have better adhesion, hardness and wear resistance; aluminum oxide can improve the density of the ceramic coating, and further improve the hardness, wear resistance, insulation, oxidation resistance and corrosion resistance of the ceramic coating; Adding yttria-stabilized zirconia can improve the strength, toughness, hardness and insulation properties of the ceramic coating, and silicon dioxide can improve the water resistance, high temperature resistance and insulation properties of the ceramic coating; the filler is made of high-expansion glass powder and silicon oxide, yttria-stabilized zirconia. The expansion of the filler in the ceramic coating changes in a gradient under thermal shock, which reduces the internal stress of the ceramic coating under thermal shock, and at the same time makes the ceramic coating have better synchronization with the soft magnetic alloy strip under thermal shock, thereby improving the adhesion of the ceramic coating, so that the ceramic coating on the soft magnetic alloy strip has high surface insulation resistance, adhesion, corrosion resistance, heat resistance and adhesion and is environmentally friendly.

[0014] The nano-composite ceramic coating liquid uses a coupling agent containing hydroxyl and / or amino groups, so that the nano-composite ceramic coating liquid has a certain viscosity, which can improve the initial adhesion performance of the nano-composite ceramic coating liquid; the emulsifier and dispersant improve the stability and uniformity of the nano-composite ceramic coating liquid; the adhesion promoter can improve the dispersion performance of the coupling agent and other components of the nano-composite ceramic coating liquid, thereby improving the uniformity and stability of the prepared ceramic coating; the mildew inhibitor makes the nano-composite ceramic coating liquid and the prepared ceramic coating have mildew and antibacterial effects.

[0015] The nano-composite ceramic coating in the present application is used in combination with a base liquid, a dispersant, a coupling agent, an adhesion promoter, an emulsifier, a mildew inhibitor and a filler. The prepared ceramic coating has a high surface insulation resistance coefficient, adhesion, good corrosion resistance, hardness and high temperature resistance; and the nano-composite ceramic coating does not contain heavy metal elements that are harmful to the human body and the environment, and is an environmentally friendly coating.

[0016] Preferably, the mixed powder of yttria-stabilized zirconium oxide and silicon oxide comprises 1-10% yttria-stabilized zirconium oxide and 1-10% silicon oxide in terms of weight percentage of the coating.

[0017] Preferably, the mixed powder of yttria-stabilized zirconia and silicon oxide comprises, by weight percentage of the coating, 5-7% yttria-stabilized zirconia and 5-10% silicon oxide; and the content of the high expansion glass powder is 1-2%.

[0018] By adopting the above technical scheme, the amount of yttria-stabilized zirconia, silicon oxide and high-expansion glass powder is optimized, and the expansion coefficient of the filler changes gradiently under the action of thermal shock, thereby reducing the internal stress of the ceramic coating, making the ceramic coating and the soft magnetic alloy substrate have better synchronization, and improving the adhesion performance of the ceramic coating on the soft magnetic alloy substrate; the prepared ceramic coating not only has a higher surface insulation resistance coefficient, better corrosion resistance, and higher hardness, but also has higher adhesion and high temperature resistance.

[0019] Preferably, the coupling agent is a composition of hydroxyl-terminated polydimethylsiloxane and aminopolydimethylsiloxane in a mass ratio of (1-3):1.

[0020] By adopting the above technical scheme, the weight and type of the coupling agent are optimized, so that the prepared ceramic coating is thinner, denser and more uniform, and thus the prepared ceramic coating has a higher surface insulation resistance, adhesion, better corrosion resistance, hardness and high temperature resistance.

[0021] Preferably, the adhesion promoter is an acrylic-cage polysilsesquioxane or a cage polysilsesquioxane containing an epoxy group.

[0022] By adopting the above technical scheme, the adhesion promoter is preferably an acrylic-cage polysilsesquioxane or a cage polysilsesquioxane containing an epoxy group, which can not only improve the dispersion performance of the components in the composite ceramic coating, but also make the prepared ceramic coating thinner, denser and more uniform; the epoxy group in the cage polysilsesquioxane containing an epoxy group has a higher reactivity, which can react with the active hydrogen in the coupling agent and / or the active hydrogen on the surface of the filler, and can enhance the interaction between the components in the nano-composite ceramic coating. The synergistic performance between the components in the ceramic coating after heat treatment is better, and the prepared ceramic coating is thinner, has a higher surface insulation resistance coefficient, adhesion, better corrosion resistance, hardness and high temperature resistance.

[0023] Preferably, the emulsifier is a nonionic surfactant; the dispersant is Dow Corning B emulsion; the mildew inhibitor is Kathon; and the solvent is at least one of an alcohol solvent, an ester solvent, and a hydrocarbon solvent.

[0024] By adopting the above technical solution, the ceramic coating prepared by the nano-composite ceramic coating liquid is more uniform and has antibacterial and anti-mildew effects.

[0025] In a second aspect, the present application provides a method for preparing a nanocomposite ceramic coating liquid: A method for preparing a nanocomposite ceramic coating liquid comprises the following preparation steps: Preparation of base liquid: Alumina and silicate powders are dispersed in a solvent at nanometer level, respectively, and then mixed, suspended and aged to obtain a nano suspension. The obtained nano suspensions are mixed to obtain a base liquid for later use; Preparation of filler suspension: Disperse yttria-stabilized zirconium oxide, silicon oxide powder and high expansion glass powder in a solvent at nanometer level, mix, suspend and ripen to obtain a nano suspension, mix the obtained nano suspensions to obtain a filler suspension for later use; Preparation of prefabricated composite coating liquid: the base liquid, the filler suspension, the dispersant and the coupling agent are mixed according to a proportion and then ground to obtain a prefabricated composite coating liquid; Preparation of nano-composite ceramic coating liquid: adding adhesion promoter, emulsifier, mildew inhibitor and remaining solvent into the prefabricated composite coating liquid according to proportion, mixing and stirring to prepare nano-composite ceramic coating liquid.

[0026] Preferably, the aging temperature is 60-120° C., and the aging time is 1-4 hours.

[0027] By adopting the above technical solution, a thin film with high surface insulation resistance, adhesion, good corrosion resistance, hardness and high temperature resistance is prepared.

[0028] After alumina, silicate powder, yttria-stabilized zirconia and silicon oxide powder are respectively infiltrated, dispersed and aged by solvent, the dispersion properties of alumina, silicate powder, yttria-stabilized zirconia and silicon oxide powder in the nano-composite ceramic coating are improved, making the prepared ceramic coating more uniform and stable, and using less dispersant and emulsifier, making the prepared ceramic coating denser (dispersant and emulsifier will carbonize and volatilize at higher temperatures such as heat treatment), thereby making the prepared ceramic coating have higher surface insulation resistivity, adhesion, better corrosion resistance, hardness and high temperature resistance.

[0029] In a third aspect, the present application provides a soft magnetic alloy strip: A soft magnetic alloy strip, comprising a soft magnetic alloy substrate and a ceramic coating; the soft magnetic alloy substrate is Permalloy, Fe-Co alloy or silicon steel; the thickness of the ceramic coating is 1-5 μm; The preparation process of the soft magnetic alloy strip is as follows: The nanocomposite ceramic coating liquid is roller coated or sprayed on the surface of the soft magnetic alloy substrate, then heated to form a film, and then heat-treated and cured to form a ceramic coating to prepare a soft magnetic alloy strip coated with a ceramic coating.

[0030] Preferably, the heat treatment conditions are selected according to the material of the soft magnetic alloy substrate in accordance with the corresponding national standards.

[0031] Preferably, the heat treatment conditions of the Permalloy are a treatment temperature of 1150-1200°C and a vacuum or argon atmosphere; the heat treatment conditions of the Fe-Co alloy are a treatment temperature of 800-900°C and a vacuum or argon atmosphere; and the heat treatment conditions of the silicon steel are a heat treatment temperature of 750-900°C and a vacuum or argon atmosphere.

[0032] By adopting the above technical scheme, the prepared ceramic coating is thinner and has less influence on the magnetism of the soft magnetic alloy substrate; the film layer is first heated before heat treatment, so that the film layer is thinner and more evenly adheres to the surface of the soft magnetic alloy substrate, so that the ceramic coating formed after heat treatment has good uniformity and density, and the prepared ceramic coating has higher surface insulation resistance coefficient, adhesion, better corrosion resistance, hardness and high temperature resistance.

[0033] In summary, this application has the following beneficial effects: 1. A nano-composite ceramic coating liquid, which uses high-expansion glass powder and silicon oxide, yttria-stabilized zirconium oxide to make the expansion coefficient of the prepared ceramic coating change gradually under the action of thermal shock, reduce the internal stress of the ceramic coating, make the ceramic coating and the soft magnetic alloy substrate have good synchronization, and then improve the adhesion of the ceramic coating, so that the prepared ceramic coating has high strength, toughness, hardness, water resistance, insulation and adhesion; further, the nano-composite ceramic coating liquid uses a coupling agent containing hydroxyl and / or amino groups to improve the stability and uniformity of the ceramic coating, and the adhesion promoter promotes the dispersion of the various components of the nano-composite ceramic coating liquid; so that the prepared ceramic coating is thin and environmentally friendly, and at the same time has a high surface insulation resistance coefficient, adhesion, good corrosion resistance, hardness and high temperature resistance.

[0034] 2. Furthermore, the amount of yttria-stabilized zirconium oxide, silicon oxide and high expansion glass powder is optimized to further improve the surface insulation resistivity and high temperature resistance of the ceramic coating.

[0035] 3. Furthermore, the weight and type of the coupling agent are optimized so that the nano-composite ceramic coating before heat treatment can better form a thinner and more uniform film layer, thereby improving the toughness, uniformity and density of the formed ceramic coating, and further improving the surface insulation resistance coefficient, adhesion, corrosion resistance, hardness and high temperature resistance of the ceramic coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is a diagram showing the adhesion of the soft magnetic alloy strip of Example 2-1 of the present invention tested by the hundred grid method; Figure 2 It is a graphical representation of the 9H pencil test hardness of the soft magnetic alloy strip of Example 2-1 of the present invention. DETAILED DESCRIPTION

[0037] raw material High expansion glass powder (expansion coefficient is about 120×10 -7 / ℃, average particle size 50nm), hydroxyl-terminated polydimethylsiloxane (viscosity 80mm at 25℃ 2 / s, hydroxyl content 2.5%), amino polydimethylsiloxane (active matter content 95%, 25℃ viscosity 100mm 2 / s). Example

[0038] Example 1-1, a nanocomposite ceramic coating liquid, the preparation method of which is as follows: Preparation of the base liquid: Alumina and solvent I are mixed, suspended and aged to obtain an alumina suspension; magnesium silicate (in other embodiments, other silicates, such as sodium silicate, may also be used) and solvent II are mixed, suspended and aged to obtain a silicate suspension; the alumina suspension and the silicate suspension are mixed, and stirred at 200±50r / min for 15±5min to obtain a nanosuspension, which is the base liquid for later use.

[0039] Preparation of filler suspension: yttria-stabilized zirconia and solvent III are mixed, suspended and matured to obtain a zirconia suspension; silicon oxide and solvent IV are mixed, suspended and matured to obtain a silicon oxide suspension; high-expansion glass powder and solvent V are mixed, suspended and matured to obtain a high-expansion glass powder nanosuspension; then the zirconia suspension, silicon oxide suspension and high-expansion glass powder suspension are stirred and mixed at 200±50r / min for 15±5min to obtain a nanosuspension, which is a filler suspension and is ready for use.

[0040] Preparation of prefabricated composite coating liquid: the base liquid, filler suspension, dispersant and coupling agent prepared above are mixed and ground multiple times by a sand mill to prepare a prefabricated composite coating liquid.

[0041] The adhesion promoter, emulsifier, mildewproof agent and the remaining amount of solvent are added to the prefabricated composite coating liquid according to the ratio, and stirred and mixed at 200±50r / min for 15±5min to obtain a total amount of 100kg nano-composite ceramic coating liquid.

[0042] Example 1-2 is a nano-composite ceramic coating liquid, which is different from Example 1-1 in that the raw material weight and preparation process parameter settings are different, as shown in Table 1; the raw material type settings are different, as shown in Table 2.

[0043] Table 1: List of raw material types, raw material weights and preparation process parameters used in the nanocomposite ceramic coating solutions of Examples 1-1 to 1-6 Table 2: List of raw material types used in the nanocomposite ceramic coating solutions of Examples 1-1 to 1-6 Examples 1-7 to 1-12 are nanocomposite ceramic coatings, which differ from Example 1-1 in that the amounts of yttria-stabilized zirconia, silicon oxide and high expansion glass powder in the filler suspension are different, as shown in Table 3.

[0044] Table 3: Table of settings for the amounts of yttria-stabilized zirconium oxide, silicon oxide, and high expansion glass powder in the filler suspension of the nanocomposite ceramic coating of Examples 1-7 to 1-12 and Example 1-1 Example 1-13 is a nano-composite ceramic coating liquid. The difference from Example 1-1 is that the coupling agent is a combination of hydroxyl-terminated polydimethylsiloxane and aminopolydimethylsiloxane in a mass ratio of 1:3.

[0045] Example 1-14 is a nano-composite ceramic coating liquid, which is different from Example 1-1 in that the coupling agent is a combination of hydroxyl-terminated polydimethylsiloxane and aminopolydimethylsiloxane in a mass ratio of 1:4.

[0046] Example 1-15 is a nano-composite ceramic coating liquid, which is different from Example 1-1 in that the coupling agent is a combination of hydroxyl-terminated polydimethylsiloxane and aminopolydimethylsiloxane in a mass ratio of 2:1.

[0047] Example 1-16 is a nano-composite ceramic coating liquid, which is different from Example 1-1 in that the coupling agent is hydroxyl-terminated polydimethylsiloxane.

[0048] Example 1-17 is a nano-composite ceramic coating liquid, which is different from Example 1-1 in that the coupling agent is aminopolydimethylsiloxane.

[0049] Example 1-18 is a nanocomposite ceramic coating liquid, which is different from Example 1-1 in that the adhesion promoter is epoxycyclohexyl-cage polysilsesquioxane.

[0050] Example 1-19 is a nano-composite ceramic coating liquid, which is different from Example 1-1 in that the adhesion promoter is glycidyl ether oxypropyl caged polysilsesquioxane POSS.

[0051] Embodiment 2-1, a soft magnetic alloy strip, the preparation process of which is as follows: The nanocomposite ceramic coating of Example 1-1 was sprayed on the surface of a soft magnetic alloy substrate (using Permalloy), then heated at 100°C for 150 min to form a film, and then heat treated (vacuum atmosphere, heat treatment temperature 1200°C, treatment time 5 h) to solidify to form a ceramic coating with a thickness of 2 μm, thereby preparing a soft magnetic alloy strip.

[0052] Figure 1 This is a diagram of the adhesion test of the soft magnetic alloy strip of Example 2-1 using the hundred-grid method. As shown in the figure: the edge of the cut is completely smooth, and there is no coating shedding in the cross-grid area.

[0053] Figure 2 It is a diagram of the 9H pencil test hardness of the soft magnetic alloy strip of Example 2-1. After the ceramic coating surface of the soft magnetic alloy strip of Example 2-1 was scratched with a 9H pencil, after wiping away the pencil marks, there was no scratch on the ceramic coating surface.

[0054] Embodiment 2-2 to Embodiment 2-4 are soft magnetic alloy strips, which differ from Embodiment 2-1 in that the nano-composite ceramic coating liquids are the nano-composite ceramic coating liquids of Embodiment 1-2 to Embodiment 1-4, respectively.

[0055] Embodiment 2-5, a soft magnetic alloy strip, the preparation process of which is as follows: The nanocomposite ceramic coating of Examples 1-5 was sprayed on the surface of a soft magnetic alloy substrate (Fe-Co alloy), then heated at 150°C for 20 min to form a film, and then heat treated (vacuum atmosphere, heat treatment temperature 900°C, treatment time 5 h) to solidify to form a ceramic coating with a thickness of 1 μm, thereby preparing a soft magnetic alloy strip.

[0056] Embodiment 2-6, a soft magnetic alloy strip, the preparation process of which is as follows: The nanocomposite ceramic coating of Examples 1-6 was sprayed on the surface of a soft magnetic alloy substrate (silicon steel), then heated at 200°C for 30 minutes to form a film, and then heat treated (argon atmosphere, heat treatment temperature 800°C, treatment time 4 hours) to solidify to form a ceramic coating with a thickness of 5 μm, thereby preparing a soft magnetic alloy strip.

[0057] Embodiment 2-7 to Embodiment 2-19 are soft magnetic alloy strips, which differ from Embodiment 2-1 in that the nano-composite ceramic coating liquids are the nano-composite ceramic coating liquids of Embodiment 1-7 to Embodiment 1-19, respectively.

[0058] Comparative Example Comparative Example 1-1, a nanocomposite ceramic coating liquid, is different from Example 1-1 in that ordinary glass powder (expansion coefficient is about 30×10 -7 / ℃, average particle size 50nm) to replace high expansion glass powder (expansion coefficient is about 120×10 -7 / ℃, average particle size 50nm).

[0059] Comparative Example 1-2 is a nanocomposite ceramic coating liquid, which differs from Example 1-1 in that an equal amount of silicon oxide is used to replace the yttria-stabilized zirconium oxide.

[0060] Comparative Example 1-3 is a nanocomposite ceramic coating liquid, which differs from Example 1-1 in that yttria-stabilized zirconium oxide is used to replace silicon oxide in an equal amount.

[0061] Comparative Example 1-4 is a nanocomposite ceramic coating liquid, which is different from Example 1-1 in that an adhesion promoter is used to replace the coupling agent in equal amounts.

[0062] Comparative Example 1-5 is a nanocomposite ceramic coating liquid, which is different from Example 1-1 in that an equal amount of a coupling agent is used to replace the adhesion promoter.

[0063] Comparative Examples 2-1 to 2-5 are soft magnetic alloy strips, which differ from Example 2-1 in that the nano-composite ceramic coating liquids are the nano-composite ceramic coating liquids of Comparative Examples 1-1 to 1-5, respectively.

[0064] Performance testing Test 1: Surface resistivity The surface resistivity of the test sample was tested in accordance with GB / T Example 1-2522-2017 "Test method for insulation resistance and adhesion of coating on electrical steel strip (sheet)".

[0065] Test 2: Adhesion performance GB / T Example 1-9286-2021 "Scratch test for paint and varnish films" tests the adhesion of the test samples.

[0066] Test 3: Thermal shock resistance The thermal shock resistance of the test samples was tested according to GB / 37246-2018 "Test Method for Thermal Shock Resistance of Fine Ceramics". The test samples were placed in a muffle furnace, heated to 600°C at a heating rate of 10°C / min, kept warm for 30 minutes, and quickly placed in a water bath for cooling, keeping the cooling water temperature at 20±3°C, cooled for 10 seconds, and taken out, dried at 110°C for 20 minutes, and naturally cooled to room temperature for 10 minutes, which is a burning / cooling operation, and the surface morphology of the ceramic coating is observed; the interval between each experiment is 30 minutes, and the burning / cooling operation is repeated until cracks or shedding appear on the surface of the ceramic coating, indicating that the coating has failed, and the number of cycles is recorded as the thermal cycle life of the ceramic coating.

[0067] Thermal shock resistance is a measure of a material's ability to resist thermal shock under drastic temperature changes, and can characterize the quality of coating adhesion.

[0068] Test 4: Salt spray test GB / T Example 1-10125-2021 "Artificial atmosphere corrosion test-Salt spray test" tests the salt spray test of the test sample.

[0069] Test 5: Pencil Hardness GB Example 1-6739-2022 "Determination of paint film hardness by pencil method for paints and varnishes" tests the pencil hardness of the test samples.

[0070] Test samples: The ceramic coatings of the soft magnetic alloy strips of Examples 2-1 to 2-19 are taken as example samples; the ceramic coatings of the soft magnetic alloy strips of Comparative Examples 2-1 to 2-5 are taken as comparative example samples.

[0071] Test results: The test results of the surface resistivity, adhesion, thermal shock resistance, salt spray test and pencil hardness of the ceramic coating of the soft magnetic alloy strips of Examples 2-1 to 2-19 and Comparative Examples 2-1 to 2-5 are shown in Table 4.

[0072] Table 4: Test results of surface resistivity, adhesion performance, thermal shock resistance, salt spray test and pencil hardness of the ceramic coating of the soft magnetic alloy strip of Examples 2-1 to 2-19 and Comparative Examples 2-1 to 2-5 Combining Examples 2-1 to 2-19 and Comparative Examples 2-1 to 2-5, and Table 4, it can be seen that: (1) The surface resistivity, thermal cycle life and adhesion performance of the soft magnetic alloy strip of Example 2-1 are better than those of Comparative Examples 1 to 5; the surface resistivity and thermal cycle life of the soft magnetic alloy strips of Examples 2-1, 2-7 and 2-8 are higher than those of Examples 2-9 to 2-12; it indicates that the coupling agent, adhesion promoter and filler are used in combination with the base liquid, dispersant and emulsifier-based mildew inhibitor in the nanocomposite ceramic coating liquid, and the filler is yttria-stabilized zirconium oxide, silicon oxide and high expansion glass powder, and the amount of each component of the filler is optimized, so that the prepared ceramic coating has higher surface insulation resistivity, adhesion, thermal shock resistance, better corrosion resistance and high temperature resistance; it may Because the filler is made of high-expansion glass powder and silicon oxide, yttria-stabilized zirconia, and the dosage of each filler component is optimized, the expansion coefficient of the prepared ceramic coating changes in a gradient under thermal shock conditions, which reduces the internal stress of the ceramic coating, makes the ceramic coating and the soft magnetic alloy substrate have better synchronization, and improves the adhesion and heat resistance of the ceramic coating on the soft magnetic alloy substrate; further, hydroxyl and / or amino coupling agents are used in the nano-composite ceramic coating to improve the stability and uniformity of the prepared ceramic coating, and the adhesion promoter promotes the dispersion of each component, so that the prepared ceramic coating is thinner and has higher surface insulation performance, adhesion performance, durability, hardness and stability, and is environmentally friendly.

[0073] (2) The surface resistivity and thermal cycle life of the soft magnetic alloy strips of Examples 2-1 and 2-13 are higher than those of Examples 2-14 and 2-17, indicating that the coupling agent using a combination of hydroxyl-terminated polydimethylsiloxane and aminopolydimethylsiloxane in a mass ratio of (1-3):1 further improves the surface resistivity and thermal cycle life of the prepared ceramic coating; probably because there is a strong interaction between hydroxyl-terminated polydimethylsiloxane and aminopolydimethylsiloxane, hydroxyl-terminated polydimethylsiloxane and aminopolydimethylsiloxane are used in the coupling agent, and their dosage is optimized, so that the nano-composite ceramic coating has better viscosity and is easier to form a uniform and stable thin film layer on the surface of the soft magnetic alloy substrate, thereby making the synergistic performance between the components of the ceramic coating formed after heat treatment better, thereby improving the surface resistivity and thermal cycle life of the prepared ceramic coating.

[0074] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A nanocomposite ceramic coating liquid, characterized in that: Calculated by weight percentage of the coating, it includes base liquid, dispersant 0.1-5%, coupling agent 2-15%, adhesion promoter 0.1-1%, emulsifier 0.2-12%, mildewproof agent 0.1-1.0%, filler 3-20% and the balance solvent; The base liquid, in terms of percentage by weight of the coating, includes 3-15% alumina, 3-25% silicate and 20-35% solvent; The filler, in terms of percentage by weight of the coating, includes 2-20% of a nano-scale yttria-stabilized zirconium oxide and silicon oxide mixed powder and 1-5% of a high expansion glass powder; The adhesion promoter is cage-shaped polysilsesquioxane; the coupling agent is at least one of hydroxyl-terminated polydimethylsiloxane and aminopolydimethylsiloxane.

2. The nanocomposite ceramic coating according to claim 1, characterized in that: The particle sizes of the yttria-stabilized zirconium oxide, silicon oxide, high expansion glass powder, aluminum oxide and silicate are all 20-100 nm.

3. The nanocomposite ceramic coating according to claim 1, characterized in that: The mixed powder of yttria-stabilized zirconium oxide and silicon oxide comprises 1-10% yttria-stabilized zirconium oxide and 1-10% silicon oxide in terms of weight percentage of the coating.

4. The nanocomposite ceramic coating liquid according to claim 3, characterized in that: The mixed powder of yttria-stabilized zirconium oxide and silicon oxide comprises 5-7% yttria-stabilized zirconium oxide and 5-10% silicon oxide in terms of weight percentage of the coating; the content of the high expansion glass powder is 1-2%.

5. The nanocomposite ceramic coating liquid according to claim 1, characterized in that: The coupling agent is a composition of hydroxyl-terminated polydimethylsiloxane and amino polydimethylsiloxane in a mass ratio of (1-3):

1.

6. The nanocomposite ceramic coating according to claim 1, characterized in that: The adhesion promoter is an acrylic-cage polysilsesquioxane or a cage polysilsesquioxane containing an epoxy group.

7. The nanocomposite ceramic coating liquid according to claim 1, characterized in that: The emulsifier is a nonionic surfactant; the dispersant is Dow Corning B emulsion; the mildew inhibitor is Kathon; and the solvent is at least one of an alcohol solvent, an ester solvent, and a hydrocarbon solvent.

8. A method for preparing the nanocomposite ceramic coating liquid according to any one of claims 1 to 7, characterized in that: The method comprises the following preparation steps: Preparation of base liquid: Alumina and silicate powders are dispersed in a solvent at nanometer level, respectively, and then mixed, suspended and aged to obtain a nano suspension. The obtained nano suspensions are mixed to obtain a base liquid for later use; Preparation of filler suspension: Disperse yttria-stabilized zirconium oxide, silicon oxide powder and high expansion glass powder in a solvent at nanometer level, mix, suspend and ripen to obtain a nano suspension, mix the obtained nano suspensions to obtain a filler suspension for later use; Preparation of prefabricated composite coating liquid: the base liquid, the filler suspension, the dispersant and the coupling agent are mixed according to a proportion and then ground to obtain a prefabricated composite coating liquid; Preparation of nano-composite ceramic coating liquid: adding adhesion promoter, emulsifier, mildew inhibitor and remaining solvent into the prefabricated composite coating liquid according to proportion, mixing and stirring to prepare nano-composite ceramic coating liquid.

9. The method for preparing the nanocomposite ceramic coating liquid according to claim 8, characterized in that: The aging temperature is 60-120° C., and the aging time is 1-4 hours.

10. A soft magnetic alloy strip, characterized in that: It comprises a soft magnetic alloy substrate and a ceramic coating; the soft magnetic alloy substrate is Permalloy, Fe-Co alloy or silicon steel; the thickness of the ceramic coating is 1-5 μm; The preparation process of the soft magnetic alloy strip is as follows: The nanocomposite ceramic coating liquid according to any one of claims 1 to 7 is roller coated or sprayed on the surface of a soft magnetic alloy substrate, then heated to form a film, and then heat treated and cured to form a ceramic coating to prepare a soft magnetic alloy strip coated with a ceramic coating.

Citation Information

Patent Citations

  • Anticorrosion insulating nano composite ceramic coating for iron-based material and preparation method thereof

    CN105694551A

  • Waterborne nano ceramic paint and preparation method thereof

    CN105985669A

  • Antibacterial wear-resistant composite non-stick pan coating and preparation method thereof

    CN112080204A

  • Nano ceramic coating and preparation method thereof

    CN114736542A